Tracing transforming honors tracks - Arts and sciences beyond borders - Peter Sonderen; Jur Koksma (Journal of the European Honors Council)
In this paper we describe how honors students of an art university and a classical research university in the east of the Netherlands, came together to work on the development of new ecologies of art and science. We narrate a yearlong learning journey by highlighting two main projects, first a local Wunderkammer project and subsequently a joint research trip to New York, Boston and Cambridge for investigating similar initiatives across the Atlantic. While going beyond the borders of disciplines and institutions, in search of new terrain, students reframe their own field as well. By experimenting with the form of our honors tracks we hope to widen the horizon of young people and help them unleash their potential. Our meandering story describes how the honors track kept on changing form, by allowing students to claim radical ownership, and how this has taught us that such experiments can not only be carried out in a responsible manner, but may also create more powerful environments for learning across borders.